American interior : the quixotic journey of John Evans, his search for a lost tribe and how, fuelled by fantasy and (possibly) booze, he accidentally annexed a third of North America, or, footnotes - a fantastical, musical quest in search of the remains of Don Juan Evans /: the quixotic journey of John Evans, his search for a lost tribe and how, fuelled by fantasy and (possibly) booze, he accidentally annexed a third of North America, or, footnotes - a fantastical, musical quest in search of the remains of Don Juan Evans. (2015) - Rhys, Gruff, 1970-
No abstract available